Increasing the efficiency by retrofitting gas boilers into a condensing heat exchanger. Issue 5 (4th May 2017) - Kovacevic, Miodrag; Lambic, Miroslav; Radovanovic, Ljiljana; Pekez, Jasmina; Ilic, Dragoljub; Nikolic, Nikola; Kucora, Istvan
ABSTRACT: When trying to reduce energy consumption in a central heating system or in a domestic water heating system, it is necessary to consider the annual operating efficiency of the heating and the domestic hot water heating system. A boiler operates under dynamic conditions, so it essential to know the methodology and the model of annual operating efficiency calculation for thermo technical systems. The outlet temperature of the flue gases with conventional gas boilers is considerably higher than the ambient temperature and consequently the heat loss occurs; it is then vented off into the environment as a result of heat transfer. The heat loss may be reduced if a condensing heat exchanger is installed, which will, on the other hand, increase the boiler efficiency by more than 10%. This paper studies the relations between combustion and heat transfer, which will enable the appraisal of a gas boiler efficiency increase and possible ways of energy savings. The method for cost-effectiveness of the investment is used to perform a feasibility study of retrofitting a conventional boiler into a condensing boiler with necessary details. The results of the investigation show that the most cost-effective temperature range of the flue gases is 40–60°C. The use of a working fluid in the heating system or the domestic cold water results in cooling the condensing heat exchanger. The temperature of the return water or the domestic cold water is lower than the water vapor dew point in the flue gases during most of the heating period in almost all parts of the Republic of Serbia where natural gas is used.